Silicon-based negative electrode material and preparation method and application thereof
Patent Information
- Application Number
- CN202611196805.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-20
AI Technical Summary
[0007]为了克服上述背景技术中硅基负极材料存在的体积膨胀大、界面稳定性差、首次库伦效率低以及循环寿命不足技术难题,本发明的目的在于提供一种硅基负极材料及其制备方法和应用;本发明采用硼酸-多巴胺-硅氧协同限域改性结构与2,4-二羟基二苯甲酮有机小分子协同界面调控体系,并结合多级碳包覆与锂硅合金化结构设计,构建具有柔性缓冲、稳定导电及界面钝化功能的多级复合结构,从而提高硅基负极材料的结构稳定性与界面稳定性;本发明制备得到的硅基负极材料具有高首次库伦效率、低极片膨胀率以及优异循环稳定性的有益效果
本发明采用硼酸-多巴胺-硅氧协同限域改性结构与2,4-二羟基二苯甲酮有机小分子协同界面调控体系对硅基负极材料进行复合改性,其中,多巴胺能够在硅颗粒表面形成具有高附着性的聚多巴胺层,硼酸能够与聚多巴胺中的邻苯二酚结构形成动态硼酸酯键,正硅酸乙酯水解后形成硅氧网络结构,三者协同作用后可在硅颗粒表面构建兼具柔性缓冲与结构稳定功能的协同限域层,从而有效缓解硅颗粒在充放电过程中的体积膨胀与界面开裂问题;同时,本发明引入传统上主要应用于紫外吸收领域、未应用于硅基负极材料界面调控体系中的2,4-二羟基二苯甲酮作为功能性有机小分子,其羟基与羰基结构能够与硅氧层形成多点氢键作用,并在热处理过程中形成富氧导电碳层,从而提高界面电子传输能力与SEI膜稳定性,降低循环过程中SEI膜反复破裂导致的活性锂消耗,表现出提高首次库伦效率与循环稳定性的意想不到效果;此外,本发明通过协同限域层、初级碳层、二次颗粒结构、次级碳层以及钝化层共同构建“锂硅合金内核-协同限域层-多级碳包覆层”复合结构,并利用氢化锂将表层氧化硅原位转化为具有较高离子传输能力的硅酸锂,同时形成锂硅合金结构,实现界面离子传输增强与原位预嵌锂协同作用,从而有效提高硅基负极材料的结构稳定性、界面稳定性、首次库伦效率以及循环稳定性。
Smart Images

Figure FT_1 
Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery anode material technology, specifically relating to a silicon-based anode material, its preparation method, and its application. Background Technology
[0002] With the rapid development of new energy vehicles, energy storage equipment, and high-end electronic products, the market has placed higher demands on the energy density, cycle life, and rate performance of lithium-ion batteries. Traditional graphite anode materials have a theoretical specific capacity of only 372 mAh / g, which is insufficient to meet the development needs of high-energy-density batteries. Silicon materials, with their high theoretical specific capacity of up to 4200 mAh / g, low lithium intercalation potential, and abundant resources, are considered one of the most promising next-generation lithium-ion battery anode materials.
[0003] However, silicon-based anode materials still face several technical bottlenecks in practical applications. First, silicon materials undergo volume expansion exceeding 300% during charge and discharge, leading to particle pulverization, conductive network breakage, and electrode structural instability. Second, the solid electrolyte interphase (SEI) film on the surface of silicon particles is prone to repeated formation and rupture during cycling, resulting in the continuous consumption of a large amount of active lithium, leading to low initial coulombic efficiency and rapid degradation of cycle performance. In addition, the poor electronic conductivity of silicon materials themselves also limits their rate performance and cycle stability.
[0004] To address the aforementioned issues, existing technologies typically employ nano-sizing, carbon coating, silicon-carbon composites, and electrolyte additive optimization to improve the performance of silicon-based anodes. For example, carbon coating can improve material conductivity and mitigate some volume expansion; constructing porous structures can provide buffer space for silicon expansion. However, existing carbon coatings are still prone to cracking due to stress concentration during long-term cycling, leading to interface instability. Furthermore, traditional interface modification methods often rely on a single coating structure, lacking a synergistic control mechanism that balances flexible buffering, ion transport, and interface stability. Therefore, it is difficult to simultaneously achieve a balance between high initial efficiency, low expansion rate, and long-term cycling stability.
[0005] In addition, most conventional organic additives in existing silicon-based anode materials are used only as ordinary binders or dispersants, and their role in regulating the interfacial chemical state and SEI film stability is limited. There is still a lack of a functional small organic molecule system that can form a stable synergistic effect with the silicon-oxygen interface and construct an oxygen-rich conductive structure after heat treatment.
[0006] Therefore, developing a silicon-based anode material and its preparation method that can simultaneously achieve interface stability, volume buffering, conductivity enhancement, and SEI film regulation is of great significance for promoting the development of high-performance semi-solid-state lithium-ion batteries. Summary of the Invention
[0007] To overcome the technical challenges of large volume expansion, poor interface stability, low initial coulombic efficiency, and insufficient cycle life inherent in silicon-based anode materials, as described in the background, this invention aims to provide a silicon-based anode material, its preparation method, and its applications. This invention employs a boric acid-dopamine-siloxane synergistic confined modification structure and a synergistic interface regulation system based on 2,4-dihydroxybenzophenone organic small molecules. Combined with multi-level carbon coating and lithium-silicon alloying structure design, a multi-level composite structure with flexible buffering, stable conductivity, and interface passivation functions is constructed, thereby improving the structural and interface stability of the silicon-based anode material. The silicon-based anode material prepared by this invention exhibits high initial coulombic efficiency, low electrode expansion rate, and excellent cycle stability.
[0008] The objective of this invention can be achieved through the following technical solutions: A silicon-based anode material comprises the following raw materials in parts by weight: 80-150 parts of nano-silicon particles; 10-50 parts of boric acid-dopamine-siloxane synergistic confinement modifier; 2-15 parts of 2,4-dihydroxybenzophenone; 3-20 parts of lithium hydride; 20-100 parts of acetylene gas; 2-15 parts of ethylene carbonate; 1-10 parts of polyacrylic acid; 3-15 parts of conductive carbon black; 20-80 parts of ethanol; and 20-100 parts of deionized water.
[0009] Optionally, the boric acid-dopamine-siloxane synergistic confinement modifier comprises the following raw materials in parts by weight: 5-25 parts dopamine; 3-20 parts boric acid; 5-30 parts tetraethyl orthosilicate; 20-80 parts ethanol; and 20-100 parts deionized water.
[0010] Optionally, the average particle size of the silicon nanoparticles is 20–100 nm.
[0011] Optionally, the silicon-based anode material has a multi-level structure of "lithium-silicon alloy core - synergistic confinement layer - primary carbon layer - secondary particles - secondary carbon layer - passivation layer".
[0012] Optionally, the thickness of the primary carbon layer is 5–50 nm, the thickness of the secondary carbon layer is 2–100 nm, and the thickness of the passivation layer is 0.1–2 nm.
[0013] Optionally, 2,4-dihydroxybenzophenone forms an oxygen-rich conductive carbon layer during heat treatment, and multi-point hydrogen bonding is formed between the hydroxyl groups and the silicon oxide layer.
[0014] Optionally, a method for preparing a silicon-based anode material includes the following steps: (1) Add dopamine to a mixed solution of ethanol and deionized water and stir at 25-45°C for 30-90 min; then add boric acid and continue the reaction for 40-120 min; then add tetraethyl orthosilicate to carry out hydrolysis and condensation reaction to obtain boric acid-dopamine-siloxane synergistic confinement modified solution. (2) Add the nano-silicon particles to the boric acid-dopamine-siloxane synergistic confinement modification solution and stir the reaction at 35-70°C for 2-6 hours to form a synergistic confinement modification layer on the surface of the silicon particles; then filter and dry to obtain modified silicon particles. (3) The obtained modified silicon particles were mixed with 2,4-dihydroxybenzophenone, ultrasonically dispersed in ethanol medium for 30-90 min, and then vacuum dried. (4) Place the obtained product in a rotary kiln, introduce acetylene gas, and pyrolyze and carbonize it at 550-800℃ for 1-4 hours to make the co-confinement layer and 2,4-dihydroxybenzophenone carbonize simultaneously to form a primary carbon coating layer. (5) The obtained particles are mixed with lithium hydride and calcined at 650-800°C for 2-6 hours under an inert atmosphere to convert the surface silicon oxide into lithium silicate and form secondary lithium-silicon alloy particles. (6) The obtained particles are subjected to chemical vapor deposition carbon coating treatment to form a secondary carbon layer on the particle surface; then ethylene carbonate is added for passivation heat treatment to obtain the silicon-based anode material.
[0015] Optionally, in step (1), the volume ratio of ethanol to deionized water is 1:1 to 4:1, and the pH of the hydrolysis-condensation reaction is 8 to 10.
[0016] Optionally, the mass ratio of lithium hydride to primary carbon-coated particles in step (5) is 0.05:1 to 1:1, and the passivation heat treatment temperature in step (6) is 200 to 350°C, and the treatment time is 2 to 8 hours.
[0017] Optionally, the application of a silicon-based anode material in a semi-solid lithium-ion battery anode.
[0018] The beneficial effects of this invention are: This invention employs a synergistic confinement modification structure of boric acid-dopamine-siloxane and a synergistic interface regulation system of 2,4-dihydroxybenzophenone organic small molecules to composite modify silicon-based anode materials. Dopamine forms a highly adhesive polydopamine layer on the silicon particle surface, boric acid forms dynamic borate ester bonds with the catechol structure in polydopamine, and tetraethyl orthosilicate hydrolyzes to form a silicon-oxygen network structure. The synergistic effect of these three components constructs a synergistic confinement layer on the silicon particle surface that combines flexible buffering and structural stability, effectively mitigating the volume expansion and interface cracking problems of silicon particles during charging and discharging. Simultaneously, this invention introduces 2,4-dihydroxybenzophenone, traditionally used primarily in the ultraviolet absorption field and not previously applied to interface regulation systems of silicon-based anode materials, as a functional organic small molecule. Its hydroxyl and carbonyl structures... It can form multi-point hydrogen bonds with the silicon oxide layer and form an oxygen-rich conductive carbon layer during heat treatment, thereby improving the interfacial electron transport capability and SEI film stability, reducing the consumption of active lithium caused by repeated SEI film rupture during cycling, and showing unexpected effects in improving the initial coulombic efficiency and cycle stability. In addition, the present invention constructs a "lithium-silicon alloy core-synergistic confinement layer-multi-level carbon coating layer" composite structure by synergistic confinement layer, primary carbon layer, secondary particle structure, secondary carbon layer and passivation layer, and uses lithium hydride to convert the surface silicon oxide in situ into lithium silicate with high ion transport capability, while forming a lithium-silicon alloy structure, realizing the synergistic effect of enhanced interfacial ion transport and in-situ pre-intercalation of lithium, thereby effectively improving the structural stability, interfacial stability, initial coulombic efficiency and cycle stability of silicon-based anode materials. Attached Figure Description
[0019] The invention will now be further described with reference to the accompanying drawings.
[0020] Figure 1 A comparison chart showing the 0.1C discharge capacity results of samples with different ratios. Detailed Implementation
[0021] The present invention will be further described below with reference to specific embodiments. However, the present invention is not limited to the following embodiments. Equivalent adjustments made without departing from the spirit and essence of the present invention should also be considered to fall within the protection scope of the present invention.
[0022] Example 1: The purpose of this example is to verify the synergistic effect between the boric acid-dopamine-siloxane co-confined structure and 2,4-dihydroxybenzophenone under moderate component content and moderate reaction conditions.
[0023] S1. Add 12 parts of dopamine to a mixed solution consisting of 50 parts of ethanol and 40 parts of deionized water, and stir at 500 r / min for 40 min at 30 °C. Then add 8 parts of boric acid and continue the reaction for 60 min to form dynamic borate ester bonds with the catechol structure in dopamine. Then add 15 parts of tetraethyl orthosilicate and adjust the pH of the system to 9 with ammonia water. React at 40 °C for 2 h to allow tetraethyl orthosilicate to undergo hydrolysis and condensation reaction to obtain a boric acid-dopamine-siloxane synergistic confinement modified solution.
[0024] S2. Add 100 parts of nano-silicon particles with an average particle size of 50 nm to the boric acid-dopamine-siloxane synergistic confinement modification solution, stir and react at 55 °C for 4 h to form a synergistic confinement modification layer on the surface of the silicon particles; then filter and dry under vacuum at 80 °C for 10 h to obtain modified silicon particles.
[0025] S3. The modified silicon particles obtained in step S2 and 6 parts of 2,4-dihydroxybenzophenone were added to ethanol and ultrasonically dispersed for 50 min. Then, they were vacuum dried at 70 °C for 8 h to allow 2,4-dihydroxybenzophenone to be uniformly adsorbed on the particle surface.
[0026] S4. Place the product obtained in step S3 in a rotary kiln, introduce acetylene gas, and pyrolyze and carbonize it at 680°C for 2 hours to simultaneously carbonize the co-confinement layer and 2,4-dihydroxybenzophenone to form a primary carbon coating layer.
[0027] S5. Take the particles obtained in step S4 and mix them with 10 parts of lithium hydride. Under argon protection, heat the mixture to 720°C and keep it at that temperature for 3 hours to convert the surface silicon oxide into lithium silicate in situ, and at the same time form secondary lithium-silicon alloy particles.
[0028] S6. The particles obtained in step S5 are placed in a rotary kiln again for chemical vapor deposition carbon coating treatment. A secondary carbon layer is formed by deposition at 620°C for 40 min. Then, 5 parts of ethylene carbonate are added and heat-treated at 300°C for 3 h to obtain silicon-based anode material.
[0029] Example 2: The purpose of this example is to verify the enhancing effect of the synergistic confinement structure and 2,4-dihydroxybenzophenone on the interface stability and cycle performance of silicon-based anode materials under optimal component content and optimal reaction conditions.
[0030] S1. Add 15 parts of dopamine to a mixed solution consisting of 60 parts of ethanol and 45 parts of deionized water, and stir at 550 r / min for 50 min at 35℃. Then add 10 parts of boric acid and continue the reaction for 70 min. After that, add 20 parts of tetraethyl orthosilicate, and adjust the pH of the system to 9 using ammonia water. React at 45℃ for 3 h to obtain a boric acid-dopamine-siloxane synergistic confinement modified solution.
[0031] S2. Add 110 parts of nano-silicon particles with an average particle size of 45nm to the synergistic confinement modification liquid, stir and react at 60°C for 5h; then filter and dry under vacuum at 85°C for 12h to obtain modified silicon particles.
[0032] S3. The modified silicon particles obtained in step S2 and 8 parts of 2,4-dihydroxybenzophenone were added to ethanol and ultrasonically dispersed for 60 min, followed by vacuum drying at 75 °C for 10 h.
[0033] S4. Place the product obtained in step S3 in a rotary kiln, introduce acetylene gas, and pyrolyze and carbonize it at 700°C for 2.5 hours to form a primary carbon coating layer.
[0034] S5. Take the particles obtained in step S4 and mix them with 12 parts of lithium hydride. Under argon protection, heat the mixture to 750°C and keep it at that temperature for 4 hours to convert the surface silicon oxide into lithium silicate and simultaneously form secondary lithium-silicon alloy particles.
[0035] S6. The particles obtained in step S5 are subjected to chemical vapor deposition carbon coating treatment, and a secondary carbon layer is formed by deposition at 650°C for 50 min; then 6 parts of ethylene carbonate are added, and the mixture is heat-treated at 320°C for 4 h to obtain silicon-based anode material.
[0036] Example 3: The purpose of this example is to verify the effect of synergistic confinement structure on rate performance and structural stability of silicon-based anode materials under higher component content and higher heat treatment conditions.
[0037] S1. Add 18 parts of dopamine to a mixed solution consisting of 70 parts of ethanol and 50 parts of deionized water, and stir at 600 r / min for 60 min at 40 °C; then add 12 parts of boric acid and continue the reaction for 90 min; then add 25 parts of tetraethyl orthosilicate, and adjust the pH of the system to 10 using ammonia water, and react at 50 °C for 4 h to obtain a boric acid-dopamine-siloxane synergistic confinement modified solution.
[0038] S2. Add 120 parts of nano-silicon particles with an average particle size of 40 nm to the synergistic confinement modification liquid, stir and react at 65 °C for 6 h; then filter and dry at 90 °C under vacuum for 12 h.
[0039] S3. The modified silicon particles obtained in step S2 and 10 parts of 2,4-dihydroxybenzophenone were added to ethanol and ultrasonically dispersed for 70 min, followed by vacuum drying at 80 °C for 10 h.
[0040] S4. Place the product obtained in step S3 into a rotary kiln, introduce acetylene gas, and pyrolyze and carbonize it at 730°C for 3 hours.
[0041] S5. Take the particles obtained in step S4 and mix them with 15 parts of lithium hydride. Heat the mixture to 780°C under argon protection and keep it at that temperature for 5 hours.
[0042] S6. The particles obtained in step S5 are subjected to chemical vapor deposition carbon coating treatment, and a secondary carbon layer is formed by deposition at 680°C for 60 min; then 8 parts of ethylene carbonate are added, and the mixture is heat-treated at 330°C for 5 h to obtain silicon-based anode material.
[0043] Comparative Example 1: This comparative example is basically the same as Example 2, except that: boric acid is not added in step S1, and only dopamine and tetraethyl orthosilicate are used to form a common polydopamine-siloxane modified layer, while the other steps remain unchanged.
[0044] S1. Add 15 parts of dopamine to a mixed solution consisting of 60 parts of ethanol and 45 parts of deionized water, and stir at 550 r / min for 50 min at 35℃. Then add 20 parts of tetraethyl orthosilicate directly, and adjust the pH of the system to 9 using ammonia water. React at 45℃ for 3 h to obtain polydopamine-siloxane modified solution.
[0045] S2. Add 110 parts of nano-silicon particles with an average particle size of 45nm to the modified liquid, stir and react at 60°C for 5h; then filter and dry under vacuum at 85°C for 12h to obtain modified silicon particles.
[0046] S3. The modified silicon particles obtained in step S2 and 8 parts of 2,4-dihydroxybenzophenone were added to ethanol and ultrasonically dispersed for 60 min, followed by vacuum drying at 75 °C for 10 h.
[0047] S4. Place the product obtained in step S3 in a rotary kiln, introduce acetylene gas, and pyrolyze and carbonize it at 700°C for 2.5 hours to form a primary carbon coating layer.
[0048] S5. Take the particles obtained in step S4 and mix them with 12 parts of lithium hydride. Under argon protection, heat the mixture to 750°C and keep it at that temperature for 4 hours to convert the surface silicon oxide into lithium silicate and simultaneously form secondary lithium-silicon alloy particles.
[0049] S6. The particles obtained in step S5 are subjected to chemical vapor deposition carbon coating treatment, and a secondary carbon layer is formed by deposition at 650°C for 50 min; then 6 parts of ethylene carbonate are added, and the mixture is heat-treated at 320°C for 4 h to obtain silicon-based anode material.
[0050] Comparative Example 2: This comparative example is basically the same as Example 2, except that 2,4-dihydroxybenzophenone is not added in step S3, while the other steps remain unchanged.
[0051] S1. Add 15 parts of dopamine to a mixed solution consisting of 60 parts of ethanol and 45 parts of deionized water, and stir at 550 r / min for 50 min at 35℃. Then add 10 parts of boric acid and continue the reaction for 70 min. After that, add 20 parts of tetraethyl orthosilicate, and adjust the pH of the system to 9 using ammonia water. React at 45℃ for 3 h to obtain a boric acid-dopamine-siloxane synergistic confinement modified solution.
[0052] S2. Add 110 parts of nano-silicon particles with an average particle size of 45nm to the synergistic confinement modification liquid, stir and react at 60°C for 5h; then filter and dry under vacuum at 85°C for 12h to obtain modified silicon particles.
[0053] S3. The modified silicon particles obtained in step S2 are directly vacuum dried at 75°C for 10 hours without adding 2,4-dihydroxybenzophenone.
[0054] S4. Place the product obtained in step S3 in a rotary kiln, introduce acetylene gas, and pyrolyze and carbonize it at 700°C for 2.5 hours to form a primary carbon coating layer.
[0055] S5. Take the particles obtained in step S4 and mix them with 12 parts of lithium hydride. Under argon protection, heat the mixture to 750°C and keep it at that temperature for 4 hours to convert the surface silicon oxide into lithium silicate and simultaneously form secondary lithium-silicon alloy particles.
[0056] S6. The particles obtained in step S5 are subjected to chemical vapor deposition carbon coating treatment, and a secondary carbon layer is formed by deposition at 650°C for 50 min; then 6 parts of ethylene carbonate are added, and the mixture is heat-treated at 320°C for 4 h to obtain silicon-based anode material.
[0057] Comparative Example 3: This comparative example is basically the same as Example 2, except that the primary carbon coating step is omitted in step S4, while the other steps remain unchanged.
[0058] S1. Add 15 parts of dopamine to a mixed solution consisting of 60 parts of ethanol and 45 parts of deionized water, and stir at 550 r / min for 50 min at 35℃. Then add 10 parts of boric acid and continue the reaction for 70 min. After that, add 20 parts of tetraethyl orthosilicate, and adjust the pH of the system to 9 using ammonia water. React at 45℃ for 3 h to obtain a boric acid-dopamine-siloxane synergistic confinement modified solution.
[0059] S2. Add 110 parts of nano-silicon particles with an average particle size of 45nm to the synergistic confinement modification liquid, stir and react at 60°C for 5h; then filter and dry under vacuum at 85°C for 12h to obtain modified silicon particles.
[0060] S3. The modified silicon particles obtained in step S2 and 8 parts of 2,4-dihydroxybenzophenone were added to ethanol and ultrasonically dispersed for 60 min, followed by vacuum drying at 75 °C for 10 h.
[0061] S4. The acetylene pyrolysis carbonization step is omitted, and no primary carbon coating layer is formed.
[0062] S5. Take the particles obtained in step S3 and mix them with 12 parts of lithium hydride. Under argon protection, heat the mixture to 750°C and keep it at that temperature for 4 hours to convert the surface silicon oxide into lithium silicate and simultaneously form secondary lithium-silicon alloy particles.
[0063] S6. The particles obtained in step S5 are subjected to chemical vapor deposition carbon coating treatment, and a secondary carbon layer is formed by deposition at 650°C for 50 min; then 6 parts of ethylene carbonate are added, and the mixture is heat-treated at 320°C for 4 h to obtain silicon-based anode material.
[0064] Comparative Example 4: This comparative example is basically the same as Example 2, except that in step S5, lithium hydride is replaced with an equal mass of metallic lithium, while the other steps remain unchanged.
[0065] S1. Add 15 parts of dopamine to a mixed solution consisting of 60 parts of ethanol and 45 parts of deionized water, and stir at 550 r / min for 50 min at 35℃. Then add 10 parts of boric acid and continue the reaction for 70 min. After that, add 20 parts of tetraethyl orthosilicate, and adjust the pH of the system to 9 using ammonia water. React at 45℃ for 3 h to obtain a boric acid-dopamine-siloxane synergistic confinement modified solution.
[0066] S2. Add 110 parts of nano-silicon particles with an average particle size of 45nm to the synergistic confinement modification liquid, stir and react at 60°C for 5h; then filter and dry under vacuum at 85°C for 12h to obtain modified silicon particles.
[0067] S3. The modified silicon particles obtained in step S2 and 8 parts of 2,4-dihydroxybenzophenone were added to ethanol and ultrasonically dispersed for 60 min, followed by vacuum drying at 75 °C for 10 h.
[0068] S4. Place the product obtained in step S3 in a rotary kiln, introduce acetylene gas, and pyrolyze and carbonize it at 700°C for 2.5 hours to form a primary carbon coating layer.
[0069] S5. Take the particles obtained in step S4 and mix them with 12 parts of metallic lithium. Under argon protection, heat the mixture to 750°C and keep it at that temperature for 4 hours to form a lithium-silicon alloy structure in the silicon particles. However, the surface silicon oxide cannot be effectively converted into lithium silicate.
[0070] S6. The particles obtained in step S5 are subjected to chemical vapor deposition carbon coating treatment, and a secondary carbon layer is formed by deposition at 650°C for 50 min; then 6 parts of ethylene carbonate are added, and the mixture is heat-treated at 320°C for 4 h to obtain silicon-based anode material.
[0071] Comparative Example 5: This comparative example is basically the same as Example 2, except that the secondary carbon coating treatment is omitted in step S6, while the other steps remain unchanged.
[0072] S1. Add 15 parts of dopamine to a mixed solution consisting of 60 parts of ethanol and 45 parts of deionized water, and stir at 550 r / min for 50 min at 35℃. Then add 10 parts of boric acid and continue the reaction for 70 min. After that, add 20 parts of tetraethyl orthosilicate, and adjust the pH of the system to 9 using ammonia water. React at 45℃ for 3 h to obtain a boric acid-dopamine-siloxane synergistic confinement modified solution.
[0073] S2. Add 110 parts of nano-silicon particles with an average particle size of 45nm to the synergistic confinement modification liquid, stir and react at 60°C for 5h; then filter and dry under vacuum at 85°C for 12h to obtain modified silicon particles.
[0074] S3. The modified silicon particles obtained in step S2 and 8 parts of 2,4-dihydroxybenzophenone were added to ethanol and ultrasonically dispersed for 60 min, followed by vacuum drying at 75 °C for 10 h.
[0075] S4. Place the product obtained in step S3 in a rotary kiln, introduce acetylene gas, and pyrolyze and carbonize it at 700°C for 2.5 hours to form a primary carbon coating layer.
[0076] S5. Take the particles obtained in step S4 and mix them with 12 parts of lithium hydride. Under argon protection, heat the mixture to 750°C and keep it at that temperature for 4 hours to convert the surface silicon oxide into lithium silicate and simultaneously form secondary lithium-silicon alloy particles.
[0077] S6. Omit the secondary carbon coating step of chemical vapor deposition, directly add 6 parts of ethylene carbonate, and heat treat at 320℃ for 4 hours to obtain silicon-based anode material.
[0078] Performance testing: 1. Initial charge / discharge performance test method The silicon-based anode material, polyacrylic acid binder, and conductive carbon black obtained in the examples and comparative examples were added to deionized water at a mass ratio of 8:1:1 and mixed and stirred to obtain a uniform anode slurry. The obtained slurry was then uniformly coated on the surface of a copper foil current collector and vacuum dried at 80°C for 12 hours. After that, the electrode sheet was punched into a circular electrode sheet and assembled into a CR2032 type half cell in a glove box, using a lithium sheet as the counter electrode and a LiPF6 electrolyte containing fluorinated ethylene carbonate as the electrolyte. A constant current charge-discharge test was performed at 25°C using a Blue Battery Test System, with a voltage range of 0.01 to 1.5V. The initial discharge specific capacity, initial charge specific capacity, and initial coulombic efficiency were recorded to evaluate the initial lithium storage performance and interface stability of the silicon-based anode material.
[0079] 2. Cyclic stability test method After assembling the silicon-based anode materials obtained in the examples and comparative examples into half-cells, constant current charge-discharge cycle tests were conducted at 25°C using a current density of 0.2C, with a charge-discharge voltage range of 0.01–1.5V. The cells were continuously cycled 100 times, and the change in discharge specific capacity at different cycle counts was recorded. By comparing the degree of capacity decay before and after cycling and the integrity of the electrode structure after cycling, the structural stability, interface stability, and cycle life performance of the silicon-based anode materials during long-term cycling were evaluated.
[0080] 3. Electrode Expansion Rate Test Method First, the initial thickness of the negative electrode obtained in the examples and comparative examples was measured. Then, the assembled half-cell was subjected to 100 constant current charge-discharge cycles at 25°C. After the cycle, the battery was disassembled, the negative electrode was removed, and the residual electrolyte on the electrode surface was cleaned with deionized water and then dried. After that, the electrode thickness was measured again after the cycle, and the changes in electrode thickness before and after the cycle were compared to evaluate the volume expansion and structural stability of the silicon-based negative electrode material during the cycle.
[0081] 4. Ratio Performance Testing Method After assembling the silicon-based anode materials obtained in the examples and comparative examples into half-cells, constant current charge-discharge tests were conducted at 25°C with current densities of 0.1C, 0.2C, 0.5C, 1C, 2C, and 5C, respectively. Each rate condition was cycled 5 times continuously, and the test voltage range was 0.01 to 1.5V. The changes in discharge specific capacity under different rate conditions were recorded, and the test was continued at low rate conditions after the high rate cycle was completed. By comparing the capacity retention and capacity recovery under different rate conditions, the electron transport capability, ion diffusion capability, and rate stability of the silicon-based anode materials were evaluated.
[0082] Table 1. Electrochemical performance test results of silicon-based anode materials in different embodiments and comparative examples.
[0083] Table 2. Stability test results of electrode structures after cycling in different embodiments and comparative examples.
[0084] Table 3 Performance test results of different embodiments and comparative embodiments at various scales
[0085] As shown in Table 1, the silicon-based anode materials prepared in Examples 1 to 3 all exhibited high initial discharge specific capacity, initial coulombic efficiency, and cycle stability. Among them, Example 2 showed the best overall performance, with an initial discharge specific capacity of 1868 mAh / g, an initial coulombic efficiency of 92.4%, and a capacity retention rate of 94.2% after 100 cycles. Meanwhile, the electrode expansion rate was only 17.8%, indicating that the boric acid-dopamine-siloxane synergistic confinement structure constructed in Example 2 can form a more stable interfacial synergistic effect with 2,4-dihydroxybenzophenone, thereby effectively alleviating the volume expansion problem of silicon particles during cycling and improving interfacial stability and electron transport capability.
[0086] Compared to Example 2, Example 1 and Example 3 showed a slight decrease in electrochemical performance, indicating that the proportions of components in the synergistic confinement structure and the heat treatment conditions have a significant impact on the performance of silicon-based anode materials. Specifically, Example 1, due to its relatively low content of the synergistic modification components, suffered from insufficient interfacial buffering and conductive network construction capabilities. While Example 3, with its relatively high heat treatment temperature and component content, improved the material's conductivity, it also tended to cause excessive densification of some carbon layer structures, thus affecting lithium-ion transport efficiency; therefore, its overall performance was slightly lower than that of Example 2.
[0087] Comparative Example 1 shows that without the addition of boric acid to construct the dynamic borate ester synergistic structure, the initial coulombic efficiency, cycle capacity retention, and electrode expansion control of the material all significantly decreased. This indicates that the dynamic synergistic confinement structure formed by boric acid can effectively enhance the interfacial stability of silicon particles and reduce the degree of structural damage during cycling. Comparative Example 2 shows that without the addition of 2,4-dihydroxybenzophenone, the cycle stability and rate performance of the material significantly decreased. This indicates that this small organic molecule can form an oxygen-rich conductive carbon layer during pyrolysis and improve the stability of the SEI film through multi-point hydrogen bonding, thereby effectively reducing interfacial side reactions and active lithium loss.
[0088] As can be seen from Comparative Examples 3 and 5, when the primary carbon coating layer or the secondary carbon coating layer is omitted, the cycling stability, rate performance and electrode structure stability of the material are significantly reduced. This indicates that the multi-level carbon coating structure can effectively construct a continuous conductive network and alleviate the volume expansion problem of silicon particles during cycling. Among them, the primary carbon layer is mainly used to buffer the local volume change of the nano-silicon particles, while the secondary carbon layer can improve the continuity of the overall conductive network and the integrity of the particle structure.
[0089] As shown in Comparative Example 4, when lithium metal is used to replace lithium hydride, the initial coulombic efficiency, cycle stability, and rate performance of the material all decrease significantly, and the electrode expansion rate increases significantly. This indicates that lithium hydride can not only achieve lithium-silicon alloying, but also convert the surface silicon oxide in situ into lithium silicate, thereby improving the interfacial ion transport capacity and interfacial stability. In contrast, lithium metal can only achieve partial alloying and cannot effectively form a stable lithium silicate interfacial layer, resulting in poor overall performance.
[0090] In summary, this invention, through the synergistic effect of the boric acid-dopamine-siloxane synergistic confinement structure, the 2,4-dihydroxybenzophenone organic small molecule interface regulation system, and the multi-level carbon coating structure, can effectively improve the interfacial stability, conductivity, and volume buffering capacity of silicon-based anode materials, thereby significantly improving the initial coulombic efficiency, cycle stability, and rate performance, and reducing the electrode expansion rate, exhibiting excellent comprehensive electrochemical performance.
Claims
1. A silicon-based anode material, characterized in that, The raw materials include the following parts by weight: 80-150 parts of nano-silicon particles; 10-50 parts of boric acid-dopamine-siloxane synergistic confinement modifier; 2-15 parts of 2,4-dihydroxybenzophenone; 3-20 parts of lithium hydride; 20-100 parts of acetylene gas; 2-15 parts of ethylene carbonate; 1-10 parts of polyacrylic acid; 3-15 parts of conductive carbon black; 20-80 parts of ethanol; and 20-100 parts of deionized water.
2. The silicon-based anode material according to claim 1, characterized in that, The boric acid-dopamine-siloxane synergistic confinement modifier comprises the following raw materials in parts by weight: 5-25 parts dopamine; 3-20 parts boric acid; 5-30 parts tetraethyl orthosilicate; 20-80 parts ethanol; and 20-100 parts deionized water.
3. The silicon-based anode material according to claim 1, characterized in that, The average particle size of the silicon nanoparticles is 20–100 nm.
4. The silicon-based anode material according to claim 1, characterized in that, The silicon-based anode material has a multi-level structure of "lithium-silicon alloy core - synergistic confinement layer - primary carbon layer - secondary particles - secondary carbon layer - passivation layer".
5. A silicon-based anode material according to claim 1, characterized in that, The primary carbon layer has a thickness of 5–50 nm, the secondary carbon layer has a thickness of 2–100 nm, and the passivation layer has a thickness of 0.1–2 nm.
6. A silicon-based anode material according to claim 1, characterized in that, The 2,4-dihydroxybenzophenone forms an oxygen-rich conductive carbon layer during heat treatment, and multi-point hydrogen bonds are formed between the hydroxyl groups and the silicon oxide layer.
7. A method for preparing a silicon-based anode material as described in any one of claims 1 to 6, characterized in that, Includes the following steps: (1) Add dopamine to a mixed solution of ethanol and deionized water and stir at 25-45°C for 30-90 min; then add boric acid and continue the reaction for 40-120 min; then add tetraethyl orthosilicate to carry out hydrolysis and condensation reaction to obtain boric acid-dopamine-siloxane synergistic confinement modified solution. (2) Add the nano-silicon particles to the boric acid-dopamine-siloxane synergistic confinement modification solution and stir the reaction at 35-70°C for 2-6 hours to form a synergistic confinement modification layer on the surface of the silicon particles; then filter and dry to obtain modified silicon particles. (3) The obtained modified silicon particles were mixed with 2,4-dihydroxybenzophenone, ultrasonically dispersed in ethanol medium for 30-90 min, and then vacuum dried. (4) Place the obtained product in a rotary kiln, introduce acetylene gas, and pyrolyze and carbonize it at 550-800℃ for 1-4 hours to make the co-confinement layer and 2,4-dihydroxybenzophenone carbonize simultaneously to form a primary carbon coating layer. (5) The obtained particles are mixed with lithium hydride and calcined at 650-800°C for 2-6 hours under an inert atmosphere to convert the surface silicon oxide into lithium silicate and form secondary lithium-silicon alloy particles. (6) The obtained particles are subjected to chemical vapor deposition carbon coating treatment to form a secondary carbon layer on the particle surface; then ethylene carbonate is added for passivation heat treatment to obtain the silicon-based anode material.
8. The method for preparing a silicon-based anode material according to claim 7, characterized in that, In step (1), the volume ratio of ethanol to deionized water is 1:1 to 4:1, and the pH of the hydrolysis-condensation reaction is 8 to 10.
9. The method for preparing a silicon-based anode material according to claim 7, characterized in that, The mass ratio of lithium hydride to primary carbon-coated particles in step (5) is 0.05:1 to 1:1, and the passivation heat treatment temperature in step (6) is 200 to 350°C, and the treatment time is 2 to 8 hours.
10. The application of a silicon-based anode material according to any one of claims 1 to 6 in a semi-solid lithium-ion battery anode.